Tantangan Penyelesaian Sengketa Internasional melalui Investor-State Dispute Settlement (ISDS): Studi terhadap Posisi Indonesia dalam Melindungi Kepentingan Umum - Fiant Lintang (Dialogia Iuridica, 2025)
This study examines the structural challenges arising from the Investor-State Dispute Settlement (ISDS) mechanism and its impact on a country’s ability, particularly Indonesia, to protect the public interests. In practice, ISDS often positions the state in a subordinate role, where policies designed to safeguard societal rights, environmental protection, and public health become targets of foreign investor claims. The study aims to analyze structural imbalances within ISDS, assess their effects on Indonesia’s regulatory sovereignty, and explore strategies for reforming investment law to balance investor protection with public interest. The research employs a normative juridical approach, analyzing bilateral and multilateral investment agreements, arbitral decisions, and relevant national policies. The findings of this study indicate that the dominance of the investor-centric paradigm in ISDS weakens the capacity of developing states to formulate progressive public policies. Therefore, Indonesia needs to restructure its investment law instruments by emphasizing social justice, transparency, and sustainability, without diminishing legal certainty for investors. The results of this research are expected to contribute to the formulation of an investment law framework that is fair, democratic, and aligned with sustainable development.